Once upon a Time... An Encyclopedia for Successfully Using Literature with Young Children - Hurst, Carol Otis (SRA-McGraw Hill, 1990)
Intended to increase the choices available for teachers and children in the classroom, this book helps teachers deal with the ever burgeoning field of children's books. The first section of the book presents studies of more than 40 authors and illustrators whose major contributions have been to young children's literature. The studies in this section of the book include information about those people's lives, their works and awards, classroom activities, and, when possible, photographs and addresses where they can be reached. The next section of the book presents descriptions of 14 picture books along with activities, other books, and activities for those other books. The next section presents 33 themes on a variety of subjects, such as accidents, cats, art and artists, clothing, farms, friendship, nursery rhymes, snow, trees, and word play, through which teachers can bring works of fiction and nonfiction to the attention of young readers. The last section presents annotated lists of books by categories, a calendar of birthdays of authors and illustrators, ideas for literature displays, a list of publishers and their addresses, and an index. (RS)